Pengaruh nilai biosferik dan kesiapan organisasi untuk berubah terhadap perilaku ramah lingkungan karyawan industri tekstil - Murniati, Juliana; Panggabean, Hana; Benedictus, Ratri Atmoko (Konsorsium Psikologi Ilmiah Nusantara, 2025)
Environmental sustainability problems caused by human actions have been increasingly threatening our future lives. Consequently, studies on human behavior are needed for ecological improvement purposes. This study examines the personal (Biospheric Value; BV) and organizational (Organizational Readiness to Change; ORtC) factors influencing pro-environmental behavior (PEB) of 257 employees from a textile company. We applied the BV, ORtC, and PEB behavioral scales for data collection, and a regression test for analysis. Regression test results showed that both BV and ORtC contribute significantly to PEB. The results demonstrate that BV and ORtC positively correlate independently with PEB. The results of multiple regression analysis indicate that BV and ORtC simultaneously contribute significantly, approaching a medium size effect in predicting PEB. Strengthening biospheric values through communal relations (guyub) is recommended by leveraging employee gathering events as social platforms for socialization, education, and habituation of PEB in the workplace.